A Successful Partnership to Help Reduce Health Disparities at Kaiser Permanente: The Institute for Culturally Competent Care and the Kaiser Permanente School of Anesthesia - Chong, Nilda (The Permanente Journal, 2006)
An innovative partnership with the Kaiser Permanente (KP) Institute for Culturally Competent Care (ICCC) has enabled the KP School of Anesthesia (KPSA) to become one of the first nurse anesthetist programs in the western United States to incorporate a formal cultural competence curriculum into its educational program. Housed administratively in the California State University system since 1981, KPSA is a fully accredited, 24-month program that educates registered nurses to become certified registered nurse anesthetists (CRNAs). The collaboration between the ICCC and KPSA represents a unique opportunity to enhance the care student nurse anesthetists provide in ten Southern California KP hospitals. In addition to serving KP patient populations, students travel to 12 affiliated hospitals in urban and rural areas. The partnership also benefits KP: Upon graduation, 80% to 90% of the student nurse anesthetists in each graduating class join the diverse KP workforce. This article describes the genesis, evolution, and potential impact of this ongoing collaboration to reduce health disparities.